2016
DOI: 10.1111/gbb.12323
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐sequencing profiles hippocampal gene expression in a validated model of cancer‐induced depression

Abstract: To investigate the pathophysiology of cancer-induced depression (CID), we have recently developed a validated CID mouse model. Given that the efficacy of antidepressants in cancer patients is controversial, it remains unclear whether CID is a biologically distinct form of depression. We used RNA-sequencing (RNA-seq) to investigate differentially expressed genes (DEGs) in hippocampi of animals from our CID model relative a positive control model of depressive-like behavior induced with chronic corticosterone (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Several mRNA targets previously reported to be related to cancer- and drug-induced depression were affected by peripheral tumor in the present study, demonstrating parallel outcomes to those previously reported in SC tumor-bearing mice,20 with these effects being amplified in IF tumor-bearing mice. In particular, GluRs and glutamatergic modulators present on microglia (glutamate ionotropic receptor NMDA type subunit 2C [Grin2c], glutamate ionotropic receptor AMPA type subunit 4 [Gria4], gamma-aminobutyric acid type A receptor alpha 3 subunit [Gabra3], and glutamate metabotropic receptor 4 [Grm4]) were reduced across Pexidartinib- and control-treated IF and SC tumor groups, with the exception of increased Grin2c mRNA in IF tumor-bearing mice relative to sham.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Several mRNA targets previously reported to be related to cancer- and drug-induced depression were affected by peripheral tumor in the present study, demonstrating parallel outcomes to those previously reported in SC tumor-bearing mice,20 with these effects being amplified in IF tumor-bearing mice. In particular, GluRs and glutamatergic modulators present on microglia (glutamate ionotropic receptor NMDA type subunit 2C [Grin2c], glutamate ionotropic receptor AMPA type subunit 4 [Gria4], gamma-aminobutyric acid type A receptor alpha 3 subunit [Gabra3], and glutamate metabotropic receptor 4 [Grm4]) were reduced across Pexidartinib- and control-treated IF and SC tumor groups, with the exception of increased Grin2c mRNA in IF tumor-bearing mice relative to sham.…”
Section: Resultssupporting
confidence: 89%
“…Isolated hippocampi were dissociated, preserved in RNAlater, and total RNA was isolated from each sample using the RNeasy Kit (Qiagen), as described previously 20. Briefly, eluates were DNase-treated using the DNA-free Kit (DNase Treatment and Removal Reagents; Ambion) and RNA quality/purity was quantitated using spectrophotometric analysis at OD 260 /OD 280 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Analysis was carried out using a web-based platform, the Galaxy Project, as previously described. 25,26 Briefly, the FastQC tool, Tophat, Cufflinks, and Cuffmerge were applied to evaluate the quality of sequencing, align reads to the human GRCh38/hg38 assembly, create assembled transcripts, and create a transcriptome assembly, respectively. Cuffdiff was then used to assess the transcript abundance in fragments per kilobase of transcript per million mapped reads (FPKM) and to identify the differentially expressed genes (DEGs) by merging the transcriptome assembly with individual aligned reads created by Tophat.…”
Section: Methodsmentioning
confidence: 99%